1998
DOI: 10.1051/parasite/1998051079
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic activity ofMonocercomonasspp.

Abstract: Summary :The hemolytic activity of an isolate of Monocercomonas spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, Monocercomonas spp. are known to live in the large intestine and pass with the feces of squamate reptiles (Da Silva et al 1998 ). They may cause moderate depression, loss of activity and weight (Zwart et al 1984 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Monocercomonas spp. are known to live in the large intestine and pass with the feces of squamate reptiles (Da Silva et al 1998 ). They may cause moderate depression, loss of activity and weight (Zwart et al 1984 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hemolytic activity of T. vaginalis and the correlation with virulence of the strains has been described previously (Grys and Hernik 1973;Krieger et al 1983;De Carli et al 1989, 1994Dailey et al 1990;Potamianos et al 1992;Fiori et al 1993;Da Silva et al 1998).…”
Section: Introductionmentioning
confidence: 82%
“…is found in the large intestine of squamate reptiles snakes (da Silva et al 1998), and recently, some studies have isolated these species from insects. Brugerolle et al (2003) found and identified by light and electron microscopy two trichomonads of the genus Monocercomonas in the hindgut of the xylophagous blattid Parasphaeria boleiriana.…”
Section: Introductionmentioning
confidence: 99%